2014
DOI: 10.1111/bju.12823
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of joint hypermobility with urinary incontinence subtypes and pelvic organ prolapse

Abstract: ObjectiveTo test the hypothesis that joint hypermobility (JHM) is associated with specific urinary incontinence (UI) subtypes and uterovaginal prolapse. Patients and MethodsIn all, 270 women scheduled to undergo urodynamic investigations were invited to self-complete a validated five-item JHM questionnaire. Women underwent history taking, symptoms assessing via the King's Health Questionnaire and clinical examination using the Pelvic Organ Prolapse Quantification system. Associations between JHM and pelvic flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
(40 reference statements)
0
4
0
4
Order By: Relevance
“…Findings on UI were mixed, with 4 of 18 studies finding no association between either EDS or HSD and UI. Among the 14 studies reporting a positive correlation for EDS or HSD and UI, rates between 68% and 84% were reported for adult women .…”
Section: Resultsmentioning
confidence: 99%
“…Findings on UI were mixed, with 4 of 18 studies finding no association between either EDS or HSD and UI. Among the 14 studies reporting a positive correlation for EDS or HSD and UI, rates between 68% and 84% were reported for adult women .…”
Section: Resultsmentioning
confidence: 99%
“…However, another recent study [Derpapas et al, ] reported a lack of strong association of JH with UI or POP. The study involved 270 women scheduled to undergo urodynamic investigations.…”
Section: Clinical Descriptionmentioning
confidence: 99%
“…Foram avaliadas 270 mulheres e a prevalência para SHA foi de 31,1% (n=84), sendo que os sintomas urinários relatados não apresentaram diferença significativa entre as mulheres com SHA e nem entre as mulheres com SHA e sem SHA. Contudo, a análise da SHA mostra uma tendência para desenvolvimento de POP, que só se tornou significativa após ajuste para a associação negativa apresentada entre a idade e a SHA (4) . Com a finalidade de avaliar a associação entre o POP, distúrbios relacionados com o colágeno e a prevalência de POP nos membros da família, dividiram mulheres em 2 grupos (grupo POP = 110 e grupo controle = 100) para realizar análise.…”
Section: Resultsunclassified
“…O sexo feminino, idade avançada, menopausa e predisposição genética são os principais fatores de risco, podendo incluir ainda a obesidade, gravidez e paridade, ressaltando que os mecanismos relacionados à "falha" do diafragma da pelve ainda não são totalmente compreendidos (12) . Geralmente a SHA se manifesta na infância ou no início da idade adulta, podendo ser um marcador precoce de risco (4) e resultar em alterações do diafragma da pelve em mulheres (20) . Além da identificação dos principais fatores de relação das disfunções do diafragma da pelve com a SHA, o presente estudo identificou a ausência de pesquisas que divulguem sugestões de prevenção.…”
Section: Resultsunclassified
See 1 more Smart Citation